2022
DOI: 10.1155/2022/9982453
|View full text |Cite
|
Sign up to set email alerts
|

Chalcone Derivatives as Potential Inhibitors of P-Glycoprotein and NorA: An In Silico and In Vitro Study

Abstract: The human P-glycoprotein (P-gp) and the NorA transporter are the major culprits of multidrug resistance observed in various bacterial strains and cancer cell lines, by extruding drug molecules out of the targeted cells, leading to treatment failures in clinical settings. Inhibiting the activity of these efflux pumps has been a well-known strategy of drug design studies in this regard. In this manuscript, our earlier published machine learning models and homology structures of P-gp and NorA were utilized to scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…In research on antimicrobial peptides, support vector machines, random forest machine learning algorithms, deep neural networks, and convolutional neural networks have found application [139]. Previously developed machine learning models were used to screen a chemo library and identify potential drug candidates for known therapeutic targets [140]. Traditional machine learning may be used to discover antimicrobial peptides in large-scale natural known peptide libraries, while artificial neural networks may predict peptide activity against pathogens and identify highly active peptides.…”
Section: Drug Discoverymentioning
confidence: 99%
“…In research on antimicrobial peptides, support vector machines, random forest machine learning algorithms, deep neural networks, and convolutional neural networks have found application [139]. Previously developed machine learning models were used to screen a chemo library and identify potential drug candidates for known therapeutic targets [140]. Traditional machine learning may be used to discover antimicrobial peptides in large-scale natural known peptide libraries, while artificial neural networks may predict peptide activity against pathogens and identify highly active peptides.…”
Section: Drug Discoverymentioning
confidence: 99%
“…Based on this computer-based analysis, the authors identified four compounds (F29, F88, F90, and F91) potentially able to inhibit the selected efflux pumps. After the synthesis, the authors performed the validation of the identified hit compounds by in vitro tests, showing that F88 and F90 showed inhibitory potency against both transporters, with effectiveness against different Staphylococcus aureus strains overexpressing NorA and resistant to ciprofloxacin ( Le et al, 2022 ).…”
Section: Biocatalysismentioning
confidence: 99%